Efficient analysis of shear wall-frame structural systems. Issue 6 (8th July 2019) - Xia, Guiyun; Shu, Wenya; Stanciulescu, Ilinca
Abstract : Purpose: This paper aims to propose an efficient method to conduct the preliminary analyses of medium or high-rise wall-frame structural systems with vertically varying properties. To this end, a finite element is formulated to take the shear deformation of the shear wall and the constrained moment of the link beam. Design/methodology/approach: The differential equation of the structure is derived from the total potential energy. Its homogenous solutions are functions of initial parameters (deflections and inner forces). To solve the structure with vertically non-uniform properties, the authors first use the classical Timoshenko beam element and then heuristically propose a finite element that uses the initial parameter solutions as shape functions and is easier to implement. A post-processing method to compute the shear force in the frame and shear wall is developed. Modal analysis using the consistent mass matrix is also incorporated. Numerical examples demonstrate the accuracy and mesh independency of the proposed element. Findings: The shear deformation of the shear wall and the constrained moment of the link beam significantly influence the static response of the structure. Taking into account the shear deformation can eliminate the misleading result of zero-base shear force of the frame and give much better predictions of the system natural frequencies. Originality/value: The proposed method achieves higher accuracy than the classical approach most often used. The finite element formulation derived from transformations of the initial parameter solutions is simple and has superior numerical performance. The post-processing method allows for a fast determination of the shear force distributions in the shear wall and frame.